Incorporation of tetraethylorthosilicate (TEOS) in biodegradable films based on bean starch (Phaseolus vulgaris). (April 2017) - Lima, Karina Oliveira; Biduski, Bárbara; Silva, Wyller Max Ferreira da; Ferreira, Silvia Moreira; Montenegro, Lara Machado Pereira; Dias, Alvaro Renato Guerra; Bianchini, Daniela
Graphical abstract: Highlights: Hybrid films with 40% TEOS content significantly increases the Young's modulus. Hybrid films with 40% TEOS content presenting higher resistance to thermal degradation. Aging time improves the water solubility properties and water vapor permeability. Hybrid films showed more hydrophobic surface. Abstract: The starch has been investigated to obtain biodegradable films, but has disadvantages such as hydrophilicity and poor mechanical properties. The addition of inorganic materials can improve mechanical properties by the synergism of the components. The aim of this study was to obtain hybrid films of bean starch and different tetraethylorthosilicate (TEOS) content (5, 20 and 40 g⋅100 g −1 starch) as well as to evaluate the influence in the properties of films. The films were prepared by casting method with hydrolysis and condensation of TEOS in situ under a controlled pH. The films were characterized after 3 and 15 days of storage, presenting a higher value of Young's modulus for the film containing 40 g TEOS, lower melting temperature, more hydrophobic surface, and a higher resistance to degradation than starch film. Furthermore, barrier properties improved when stored for 15 days. The relative crystallinity was not affected by adding the precursor.